Salvage therapy in cancer patients with hepatitis C without sustained virologic response after direct‐acting antivirals—A prospective study. Issue 3 (19th December 2019) - Pritchard, Haley; Jandhyala, Deeksha; Hosry, Jeff; Angelidakis, Georgios; Torres, Harrys A
Abstract : Background and Aim: No information exists regarding direct‐acting antivirals (DAAs) salvage therapy for Hepatitis C (HCV)‐infected patients with any type of cancer. We prospectively evaluated the safety and efficacy (SVR12) of salvage therapy in these patients. Methods: Patients who failed initial DAAs (01/2015–01/2018) were analyzed. Resistance‐associated substitutions to NS5A and NS3 were investigated by population sequencing. Results: Of 164 patients enrolled, 16 (10%) experienced treatment failure. Of these, 11 patients received salvage therapy. The majority (91%) were men; 55% had genotype 1a, 45% had cirrhosis, and 45% had hepatocellular carcinoma. Four patients failed the first salvage therapy, and two of them required a second salvage therapy. Overall, 9 of 11 (82%) patients achieved SVR12. All four patients treated with sofosbuvir/velpatasvir/voxilaprevir (+/− ribavirin) achieved SVR12. The presence of resistance‐associated substitutions did not impact response. Seven patients developed grade 1/2 adverse events. No patient had grade 3/4 adverse events. No patient required interruption of DAA therapy because of clinical or laboratory abnormalities. Conclusions: This is the first prospective study in HCV‐infected cancer patients failing DAAs. The efficacy of salvage therapy in this group appears to be lower than previously reported in non‐cancer patients, but better response rates are observed with newer regimens. Salvage therapy is associated with minimal toxicity. Abstract : This is the first prospective study in HCV‐infected cancer patients failing direct‐acting antivirals. The efficacy of salvage therapy in this group appears to be lower than the previously reported in non‐cancer patients but better response rates are observed with newer regimens. Salvage therapy is associated with minimal toxicity.